Принципи формування архітектурної типології і проєктування міжуніверситетських культурних центрів - Дмитраш, Ольга Юріївна (Національний університет "Львівська політехніка", 2021)
У дисертації проведений аналіз джерельної бази та історичних етапів формоутворення архітектури будівель об’єктів культури у складі університетів світу. Розроблено тлумачення поняття міжуніверситетський культурний центр і навчальний простір з гнучким плануванням. Проаналізовано та узагальнено світовий досвід проектування, будівництва та експлуатації даних об’єктів та визначені основні чинники, що впливають на їх формоутворення та типологію, проведено аналіз існуючої нормативної бази, запропоновано класифікацію існуючих типів. Теоретично обґрунтовані принципи та засоби формування архітектурно-планувальної організації міжуніверситетських культурних центрів. Розроблено класифікацію МУКЦ за типами, функціональне зонування території і схему загальної функціональнопланувальної організації приміщень МКЦ. Рекомендовано доповнити ДБН В. 2.2-3-2018 розробленими у роботі положеннями. Визначено найсприятливіші міста України для розташування в них різного типу студентських культурних центрів. Подано рекомендації щодо принципів розташування міжуніверситетських центрів у містах. Розроблено пропозиції щодо адаптації існуючих об’єктів культури при університетах України. В диссертации проведен анализ источниковой базы и исторических этапов формообразования архитектуры зданий объектов культуры в составе университетов мира. Разработано толкование понятия межуниверситетский культурный центр и учебное пространство с гибкой планировкой. Проанализирован и обобщен мировой опыт проектирования, строительства и эксплуатации данных объектов и определены основные факторы, влияющие на их формообразования и типологию, проведен анализ существующей нормативной базы, разработана классификация существующих типов. Теоретически обоснованы принципы и средства формирования архитектурно-планировочной организации межвузовских культурных центров. Разработана классификация МКЦ по типам, функциональное зонирование территории и схема общей функционально-планировочной организации помещений МКЦ. Рекомендуется дополнить ДБН 2.2-3-2018 разработанными в работе положениями. Определены самые благоприятные города Украины для размещения в них различного типа культурных центров. Даны рекомендации по принципам расположения студенческих центров в городах. Разработаны предложения по адаптации существующих объектов культуры при университетах Украины.The Interuniversity Centre of Culture (IUCC) is a new term in the national architectural dictionary. Buildings of this type are widely popular around the world. These institutions represent the needs and priorities for the development of modern higher education. For the first time, the historical aspect of the formation of the architecture of cultural objects in universities and defining the chronological boundaries of the study is highlighted, and at different times there was a distinct understanding of the needs of cultural development of students, which was reflected in architecture. The analysis of the theoretical basis of designing cultural objects at universities shows that today in the domestic professional literature this topic has been insufficiently covered, which leads to the impossibility of implementing a positive world experience in Ukraine. The author has developed an interpretation of the concept of the Interuniversity Cultural Centre – a multifunctional institution designed for cultural and educational, sports, entertainment, scientific and educational, and leisure activities, activities of which are aimed at implementing cooperation between higher education institutions. Learning Space with flexible planning – rooms and areas designed for studies in free time outside of formal study rooms (classrooms, lecture halls), which can transform and adapt to different needs. The architectural and planning organization of modern IUCC should embody the ideas of the educational space with flexible planning. The general scientific theoretical methods used in the thesis have been determined and substantiated. The organizational structure of work has been developed, which is formed by consistent use of research methods. The basis of the empirical base of the study has been determined – 55 cultural objects as part of the universities of the world, 7 cultural objects as part of the universities of Ukraine. Questionnaires were conducted in three groups, which allowed to confirm the relevance of the research topic, to determine the inconsistency of existing institutions with the needs of their users. A comparative analysis of domestic and foreign experience in the construction and operation of cultural facilities at universities allowed us to identify the main differences in approaches to the design of these buildings. It should be noted that the main criterion for the success of IUCC is the high intensity of their use, which is due to the foreign experience of inclusion of food and drink venues and sales areas in the group of main facilities. Besides, an important argument is daily access to the facilities seven days a week, a large number of entrance spaces, the use of training areas with flexible planning in the planning structure. A study of the existing regulatory framework, which enabled to identify the shortcomings of the regulatory framework for the design of the IUCC and revealed to the need to supplement SCS B. 2.2-3-2018. Today in Ukraine, there are no norms for designing interuniversity cultural centres, which in turn determines the need for the study of such public facilities, development of typological classification and layout of such complexes in the city structure. The following classification features and main functions of existing types of buildings of cultural objects for students have been revealed. The main factors have been determined: socio-economic factor, urban development factor, functional factor, architectural and spatial factor. The basic principles of the building typology of IUCC have been formed: principle of individualization and generalization, principle of adaptability, principle of multifunctionality, principle of the aestheticization. It is recommended to supplement the regulatory framework, namely - SCS B. 2.2-3-2018, to introduce the concept of Interuniversity Cultural Centre, also to include the concept of educational space with flexible planning in this normative document. For the first time, the classification of IUCC by types was developed: cultural and leisure, sports and entertainment, religious and educational, research. The recommended functional zoning of the site for the IUCC design has been developed. For the first time, the basic principles of the location of the IUCC building in the planning structure of the university campus have been presented. The main elements of the functional zoning of IUCC buildings have been formed.The scheme of the general functional-planning organization of the IUCC premises. For the first time, a theoretical model of the location of the IUCC on the territory of Ukraine has been presented. Using Lviv city as an example, an algorithm for selecting a site for the IUCC design has been demonstrated. Strategies for the location of such institutions in the structure of university campuses in Ukraine have been developed: centralized, focused, distributed.
Принципы формирования архитектурной типологии и проектирование межвузовских культурных центров
Principles of formation of architectural typology and design of interuniversity cultural centres
Keywords: архітектурна типологія; чинники, принципи та засоби в архітектурі; культурно-видовищні заклади; вищий навчальний заклад; міжуніверситетський культурний центр; навчальний простір з гнучким плануванням; архитектурная типология; факторы, принципы и средства в архитектуре; культурно-зрелищные учреждения; высшее учебное заведение; межуниверситетский культурный центр; учебное пространство с гибкой планировкой; building typology; factors, principles and means in architecture; cultural and entertainment establishments; higher educational establishment; interuniversity cultural centre; educational space with flexible planning; 711.16:72.05